2010
DOI: 10.1021/jp101841b
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of the CO2 + K/Au(111) System

Abstract: Photoinduced activation of CO 2 was investigated on a K-dosed Au(111) surface. The methods used were work function measurements, high-resolution electron energy loss spectroscopy (HREELS), and thermal desorption spectroscopy. Illumination of CO 2 adsorbed on a clean Au(111) surface with a 65 W Hg arc lamp produced no HREEL spectral signals indicative of the formation of CO 2 -. As was revealed in a previous paper (Farkas and Solymosi, J. Phys. Chem. C 2009, 113, 19930), potassium adatoms induce the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As known CO 2 is a very stable molecule. In previous studies performed on TiO 2 -supported metals [27] and metal single crystals including Au(1 1 1) [28][29][30][31], it was revealed that the donation of electrons from the catalyst to the antibonding p level of CO 2 leads to the formation of reactive negatively charged CO 2 dÀ . Based on this consideration we propose the occurrence of following steps for the reaction of CO 2 and C 2 H 6…”
Section: Discussionmentioning
confidence: 99%
“…As known CO 2 is a very stable molecule. In previous studies performed on TiO 2 -supported metals [27] and metal single crystals including Au(1 1 1) [28][29][30][31], it was revealed that the donation of electrons from the catalyst to the antibonding p level of CO 2 leads to the formation of reactive negatively charged CO 2 dÀ . Based on this consideration we propose the occurrence of following steps for the reaction of CO 2 and C 2 H 6…”
Section: Discussionmentioning
confidence: 99%
“…For the optimization of the TS structure, we introduced the image function method together with the level-shift Newton-Raphson method. 38,39 This procedure is effective when one uses an appropriate initial guess, which is close to the transition-state (TS) structure.…”
Section: Theoretical Background: Ap Methodsmentioning
confidence: 99%
“…importance of the activation of CO 2 appeared in our recent study dealing with the catalytic and photocatalytic reaction of H 2 þ CO 2 on Au deposited on various n-type oxides [52,53].…”
Section: Catalytic Studymentioning
confidence: 99%